EvaluatIon of toxIcItIes seen In young and older chIldren [Altı yaş ve altındaki çocuklarda ve altı yaşından büyük çocuklarda karşılaşılan zehirlenmelerin araştırılması] - (:unkn) unknown (Marmara University, 2013)
All children may face intoxication with drugs and other substances. In this study, it was aimed to investigate the children hospitalized with toxicities at pediatric clinic in a hospital. Children were divided into two groups according to the age, i.e. 6 years and younger and older than 6. Seventy five medical records of hospitalized children, diagnosed with toxicity during year of 2011, were evaluated retrospectively in Pediatric Clinic, Haydarpaşa Numune Training-Research Hospital. Substances and causes of toxicities, timing of toxicity, admitting time to hospital, duration of hospitalization, prognosis and patients' demographic characteristics were evaluated. Cases between 2-6 year ages (younger group) were compared with the ones aged between 7-15 year (older group). There was no deaths due to toxicity in the study period. The main cause was drug intoxication with 88% (most frequent drug was paracetamol, 13.8%) and the most common drugs were neurological agents (52.9%). Mainly causes of toxicities were accidents (80%) and suicides (18.7%). The incidence of intoxications seen in girls (50.7%) was nearly the same with the ones in boys, but total intoxications due to suicides were more frequent in girls (85.7%) than the boys. Boys were higher in younger group although girls were higher in older group (p<0.05). Following intoxications, younger children were admitted to the hospital earlier than the older ones (p<0.05). Age related differences are important in childhood toxicities. Managements are required to enlighten children and their parents to pay attention for intoxications with drugs especially affecting the neurological sign.
Keywords: Children; Medicine; Six-year old; Suicide; Toxicity